1995
DOI: 10.1111/j.1476-5381.1995.tb13378.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization of tripitramine, a polymethylene tetraamine displaying high selectivity and affinity for muscarinic M2 receptors

Abstract: 1 The antimuscarinic effects of tripitramine were investigated in vitro in isolated driven left (force) and spontaneously beating right (force and rate) atria as well as in the ileum of guinea-pig and rat and in the trachea and lung strip of guinea-pig and compared with the effects of methoctramine. 2 Tripitramine was a potent competitive antagonist of muscarinic M2 receptors in right and left atria. The pA2 values ranged from 9.14 to 9.85. However, in the guinea-pig and rat left atria but not in guinea-pig ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 39 publications
2
12
3
Order By: Relevance
“…Saturation experiments were conducted with eight concentrations of radioligand (0.04–5 n M ) and most competition displacement curves were generated with six concentrations of antagonists. To define M 2 and M 3 receptor proportions, 24 concentrations of tripitramine, a muscarinic antagonist with a marked degree of selectivity for M 2 over M 3 receptors ( Chiarini et al ., 1995 ; Roffel et al ., 1997 ), were used. Incubations were carried out to equilibrium (60 min at room temperature).…”
Section: Methodsmentioning
confidence: 99%
“…Saturation experiments were conducted with eight concentrations of radioligand (0.04–5 n M ) and most competition displacement curves were generated with six concentrations of antagonists. To define M 2 and M 3 receptor proportions, 24 concentrations of tripitramine, a muscarinic antagonist with a marked degree of selectivity for M 2 over M 3 receptors ( Chiarini et al ., 1995 ; Roffel et al ., 1997 ), were used. Incubations were carried out to equilibrium (60 min at room temperature).…”
Section: Methodsmentioning
confidence: 99%
“…In human detrusor muscle, M2 receptors existed three times more than M3 receptors according to the immunoprecipitation study [13]. The receptor binding assay also indicated that the percentages of M2 and M3 receptors were 60% -80% and 20% -40%, respectively [14,15]. Braverman et al reported that M2 muscarinic receptor contributed to rat urinay bladder contraction [16].…”
Section: Muscarinic Receptor-mediated Bladder Contraction In Body Andmentioning
confidence: 99%
“…However, in the guinea pig and rat left atria, but not in guinea pig right atria, tripitramine at lower concentrations (3-10 nM) produced a less than proportional displacement to the right of agonist-induced responses owing to the presence of a possible saturable removal process. 44 Tripitramine was about three orders of magnitude less potent in ileal and tracheal than in atrial preparations (pA 2 values ranging from 6.34 to 6.81) which makes it more potent and more selective than methoctramine. Furthermore, tripitramine was more specific than methoctramine because, in addition to muscarinic receptors, it inhibited only frog rectus abdominis muscular (pIC 50 , 6.14) and rat duodenum neuronal (pIC 50 , 4.87) nicotinic receptors among the set of receptor systems investigated, namely a 1 -, a 2 -, and b 1 -adrenoceptors, H 1 -, and H 2 -histamine receptors, and muscular and neuronal nicotinic receptors.…”
Section: Biological Propertiesmentioning
confidence: 98%
“…Furthermore, tripitramine was more specific than methoctramine because, in addition to muscarinic receptors, it inhibited only frog rectus abdominis muscular (pIC 50 , 6.14) and rat duodenum neuronal (pIC 50 , 4.87) nicotinic receptors among the set of receptor systems investigated, namely a 1 -, a 2 -, and b 1 -adrenoceptors, H 1 -, and H 2 -histamine receptors, and muscular and neuronal nicotinic receptors. 44 The antimuscarinic effects of tripitramine were assessed also in in vivo preparations, namely, anaesthetized and pithed rats. Tripitramine (0.0202 mmol/kg i.v.)…”
Section: Biological Propertiesmentioning
confidence: 99%